Climate change threatens the most biodiverse regions of Mexico. (December 2019) - Esperon-Rodriguez, Manuel; Beaumont, Linda J.; Lenoir, Jonathan; Baumgartner, John B.; McGowan, Jennifer; Correa-Metrio, Alexander; Camac, James S.
Highlights: Across 40 protected areas, temperature is predicted to increase ∼3 °C by 2050. 31 protected areas are predicted to lose 100% of their baseline climatic space. 17 protected areas may lose climate variability (homogenization), decreasing species' niches. The effect of non-analogue conditions on species and ecosystems is largely unknown. We propose a vulnerability index to categorise natural protected areas. Abstract: Climate change threatens Earth's biodiversity, although its impacts are variable and depend on the capacity of species and ecosystems to cope with the magnitude and speed of change. Natural protected areas (NPAs) constitute potential refugia for species' persistence and for sustaining the provisioning of ecosystem services. Biosphere reserves are NPAs that are less altered by human actions and provide habitat to endemic, threatened or endangered species. Here, we aim to evaluate the threat imposed by climate change on the network of biosphere reserves in Mexico. Focusing on five bioclimatic variables, we computed the climatic space – measured as an n -dimensional hypervolume – of 40 NPAs. Increases in temperature are predicted for all NPAs by 2050, whereas decreases in annual rainfall are predicted for 30 NPAs. By 2050, 31 NPAs that provide habitat to 22, 866 recorded species are predicted to lose 100% of their baseline climatic space, shifting to completely novel climates. On average, the other nine NPAs are predicted to lose 55.7% (SD = 26.7%) of their baseline climatic space, while 54.5% (SD = 32.5%) of the future climatic space will be novel. Seventeen NPAs may lose climate variability (homogenization), decreasing species' niches. The extent to which non-analogue conditions will remain within the tolerance of species and ecosystems is currently unknown. Finally, we propose a vulnerability index to categorise NPAs based on their loss of existing climatic space, total geographic area, species richness, and uniqueness of species composition, finding los Tuxtlas and Tiburon Ballena as the most and least vulnerable NPAs, respectively. Graphical abstract: